Flipped classroom in physics teacher education: (how) can students' expectations be met? - Bitzenbauer, Philipp; Hennig, Fabian (Frontiers in Education, 2023)
In this paper, we describe the development of a flipped classroom concept for physics teacher education along (a) design criteria from the literature, and (b) students' needs and expectations extracted from an exploratory pre-study (N = 21). We implemented it in a physics education course at Leipzig University, Germany, and report results of its empirical evaluation (N = 29). Our results hint at both, strengths and weaknesses of the developed flipped classroom concept, and hence, pave the way for further research into the use of flipped classroom scenarios in physics teacher education.